Perceived racial discrimination, childhood adversity, and self-reported high blood pressure among adults in rural Alabama - Littleton, Tenesha; Cosenzo, Luciana Giorgio; Okine, Joana; Newman, Sharlene D. (Frontiers in Public Health, 2025)
IntroductionDisproportionate exposure to psychosocial stressors, such as racial discrimination, and other forms of adversity across the life course contributes to higher rates of hypertension among Black Americans. However, prior literature is limited by the underrepresentation of rural populations and narrow measurements of racial discrimination. This study examines associations between perceived racial discrimination (through a historical trauma lens), childhood adversity, and self-reported high blood pressure among adults living in predominantly Black communities in rural Alabama.MethodsData were collected using paper-and-pencil surveys from 184 participants across five rural communities in Alabama in Spring 2023. High blood pressure was assessed via self-report from a list of chronic conditions. Perceived racial discrimination was measured by a 5-item subscale of the African American Historical Trauma Questionnaire. Childhood adversity was measured by the 10-item ACE Study Questionnaire. Binary logistic regression examined associations between high blood pressure, childhood adversity, and perceived racial discrimination, adjusting for psychological distress and sociodemographic factors.ResultsNinety-two percent of the sample were Black Americans. Older age (OR = 1.09, 95% CI = 1.05, 1.12) and higher perceived racial discrimination scores (OR = 1.15, 95% CI = 1.04, 1.27) were significantly associated with increased odds of high blood pressure.DiscussionFindings highlight the importance of multilevel interventions that are both trauma-informed and culturally tailored to reduce health disparities in rural Black communities.